Breeder at Law - Momberger, Karla (Columbia Journal of Gender and Law, 2002)
I realized soon into this project that the most difficult part might be identifying what, exactly, this paper is about. It’s not that easy to do, especially when everything seems so connected. But you should be aware that I am writing from an extremely confident perspective; today I got a fortune in a cookie that says: Everyone agrees you are the best. Well, if everyone agrees, it must be true-isn’t my existence a series of reflections off other people? This paper is about an embodied law school experience, and what that experience indicates about corporeality in the legal system in general. It’s about paying for school with my body. What price is exacted is uncertain. It’s about existing in a body that is out of bounds, and about becoming the multiple reflections of how others perceive my embodiedness. It’s about the bizarre realm of biotechnology, infertility, and reproduction. It’s about the ways that gender, race, class, and sexuality interplay in this arena. It’s about learning to negotiate your value in the very specific terms of the dollar amount your genetic inheritance is worth. It’s about how the dollar value changes based on who you are, and who you are perceived to be. This paper is also about fighting with your Mom. It’s about knowing you have a steep hill to climb in order to gain legitimacy in traditional ways, and what it means to try to go around that hill. This story is about learning to police yourself, about living in a modem, technologically-dependent society. It’s about what it means to be a polluter in such a society, and how pollution rituals weave the fabric of society. It’s about why the law echoes, creates, and recreates that fabric of pollution and purity.